2004
DOI: 10.1161/01.cir.0000147827.43912.ae
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Stimulates Myocardial Perfusion In Vivo

Abstract: Background-Several clinical studies have demonstrated a close association between plasma HDL cholesterol levels and endothelium-dependent vasodilation in peripheral arteries. In isolated arteries, HDL has been shown to mediate vasodilation via NO release. In vivo, administration of reconstituted HDL restored abnormal endothelial function of the brachial artery in hypercholesterolemic patients. However, no data are currently available on the effect of HDL on myocardial perfusion. Methods and Results-In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 30 publications
4
63
0
Order By: Relevance
“…These findings also indicate that minor components of HDL, namely estrogen and sphingosine-1-phosphate (S1P), which have been previously implicated in eNOS activation (35,36), are most likely minimally involved in this pathway. This conclusion is consistent with the observations that HDL activates eNOS in cells devoid of estrogen receptors (14) and that it stimulates myocardial perfusion in mice deficient for the S1P receptor S1P 3 (34). Confirmation of the importance of cholesterol efflux was then obtained in studies of wild-type SR-BI versus the AVI mutant (22), in which the capacity of AVI to mediate efflux to HDL but not to SUVs was paralleled by an ability to signal to eNOS in response to HDL but not to SUV.…”
Section: Discussionsupporting
confidence: 90%
“…These findings also indicate that minor components of HDL, namely estrogen and sphingosine-1-phosphate (S1P), which have been previously implicated in eNOS activation (35,36), are most likely minimally involved in this pathway. This conclusion is consistent with the observations that HDL activates eNOS in cells devoid of estrogen receptors (14) and that it stimulates myocardial perfusion in mice deficient for the S1P receptor S1P 3 (34). Confirmation of the importance of cholesterol efflux was then obtained in studies of wild-type SR-BI versus the AVI mutant (22), in which the capacity of AVI to mediate efflux to HDL but not to SUVs was paralleled by an ability to signal to eNOS in response to HDL but not to SUV.…”
Section: Discussionsupporting
confidence: 90%
“…induced a rapid and transient decrease in heart rate (HR) and MABP in rats (Sugiyama et al, 2000). However, these findings were disputed by others (Bischoff et al, 2000b;Levkau et al, 2004). In a subsequent study, Nofer et al (2004b) confirmed that S1P induced transient hypotension in mice pretreated with ET-1 to raise BP.…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 96%
“…A clear role for S1P 3 has also been demonstrated in the regulation of heart rate in rodents (Forrest et al, 2004;Sanna et al, 2004), and it has been shown to regulate lymphoid endothelial cells (Girkontaite et al, 2004) and to have effects on endothelial progenitor cells (Walter et al, 2007). S1P 3 regulates myocardial perfusion and provides protection in ischemia-reperfusion injury (Levkau et al, 2004;Theilmeier et al, 2006;Means et al, 2007) and further influences vasorelaxation (Nofer et al, 2004) and cardiac fibrosis (Takuwa et al, 2009). Other influences on myofibroblasts (Keller et al, 2007), as well as S1P 3 links to PAR-1 signaling that couples coagulation events with inflammation (Niessen et al, 2008), have been reported.…”
Section: B Sphingosine 1-phosphate Receptorsmentioning
confidence: 99%